Does trade facilitation challenge the domestic logistics enterprises in Vietnam? - Phan, Thị Thu Hiền (Journal of International Economics and Management, 2019)
This study comes from the theme of World Customs Organization “Trade facilitation initiatives and intergovernmental schemes of customs community have been providing logistics enterprises with many opportunities to join effectively and profitably in the integrated supply chains all over the world” (World Customs Organization, 2016). Authorized Economic Operator (AEO) and AEO Mutual Recognition Agreements (AEO MRAs) are the security and trade facilitation initiatives aiming to enhance global trade security and foster business competitiveness in many countries. In principle, this initiative helps well-regulated enterprises to gain priorities in trade and supply chain operations provided that they adequately meet the criteria of the AEO program. However, the Vietnamese logistics companies cannot gain benefits from the AEO program due to specific requirements of doing international trade transactions like very high exports and imports turnover as well as big volume of customs declarations. That is why there is no Vietnamese logistics company who has been granted AEO status by the end of 2018 (GDVC, 2018). This study aims to figure out the reality that the Vietnam’s current AEO program is highly challenging the Vietnamese logistics companies.